Application of olefin metathesis in the synthesis of functionalized polyhedral oligomeric silsesquioxanes (POSS) and POSS-containing polymeric materials - Żak, Patrycja; Pietraszuk, Cezary (Beilstein Journal of Organic Chemistry, 2019)
This mini-review summarizes the applications of olefin metathesis in synthesis and functionalization of polyhedral oligomeric silsesquioxanes (POSS) and POSS-containing polymeric materials. Three types of processes, i.e., cross metathesis (CM) of vinyl-substituted POSS with terminal olefins, acyclic diene metathesis (ADMET) copolymerization of divinyl-substituted POSS with α,ω-dienes and ring-opening metathesis polymerization (ROMP) of POSS-substituted norbornene (or other ROMP susceptible cycloolefins) are discussed. Emphasis was put on the synthetic and catalytic aspects rather than on the properties and applications of synthesized materials.
Keywords: olefin metathesis; POSS; silsesquioxanes